The state of children's health and the formation of health competence in schoolchildren living in iodine-deficient regions - T.V. Sorokman; M.I. Bachu; M.G. Gingulyak (Zaslavsky O.Yu., 2021)
Background. Iodine deficiency in the diet is the only and most common cause of brain damage and intellectual impairment in children, which can be prevented by adequate methods. The purpose was to assess the state of health of children and the formation of health competence in schoolchildren living in iodine-deficient regions. Materials and methods. Six hundred and fifty-five parents were surveyed and the morbidity was retrospectively studied in 1,973 schoolchildren from different districts of Northern Bukovina (Chernivtsi region). Integrated awareness indicator (IAI) and integrated preventive behavior indicator (IPBI) have been identified. Results. The nutrition of the examined children was irrational, with the use of products grown on homesteads, iodized salt was used by only 1 family out of 50. 11.9 % of respondents rated their health as excellent (not sick), 71.7 % - as good (sometimes sick), 16.3 %- as satisfactory (often ill). 14.4 % of respondents have a high IPBI, 41.7 % - a medium and 43.8 % have a low IPBI. There is a highly reliable relationship between IAI and IPBI (Pearson λ2 = 98.119, df = 29, p = 0.000, Cramer's V = 0.162). Conclusions. In order to develop health competence in schoolchildren living in iodine-deficient regions, it is necessary to develop and implement new forms of motivation for daily preventive intake of iodized salt.